2017
DOI: 10.1177/1475725717719771
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing Flashcards to Increase Student Learning

Abstract: Two studies examined the effectiveness of a flashcard-based study strategy, Flashcards-Plus, in an ecologically valid context. The strategy requires students to create flashcards designed to increase their ability to retain, comprehend, and apply textbook material to exams. In Studies 1a (n ¼ 73) and 1b (n ¼ 62), we introduced all students to the Flashcards-Plus method and compared their exam scores. Students who used this strategy scored significantly higher than those who did not. In Study 2 (n ¼ 434), we ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
(29 reference statements)
2
18
0
2
Order By: Relevance
“…For example, Schmidmaier et al (2011) found that medical students who engaged in repeated testing with flash cards were able to recall more medical terms on a test after a 1-week delay than students who engaged in repeated studying. Likewise, Golding, Wasarhaley, and Fletcher (2012) found that students who reported using flash cards more often scored higher on exams in an introductory psychology course, and Senzaki, Hackathorn, Appleby, and Gurung (2017) showed that students who were randomly assigned to receive a short lecture on the use of flash cards, incorporating generation of flash cards and tying the content to their own experience, scored higher in the term exams.…”
Section: Effective Implementationmentioning
confidence: 99%
“…For example, Schmidmaier et al (2011) found that medical students who engaged in repeated testing with flash cards were able to recall more medical terms on a test after a 1-week delay than students who engaged in repeated studying. Likewise, Golding, Wasarhaley, and Fletcher (2012) found that students who reported using flash cards more often scored higher on exams in an introductory psychology course, and Senzaki, Hackathorn, Appleby, and Gurung (2017) showed that students who were randomly assigned to receive a short lecture on the use of flash cards, incorporating generation of flash cards and tying the content to their own experience, scored higher in the term exams.…”
Section: Effective Implementationmentioning
confidence: 99%
“…Textbooks may include pre-written flashcards for students, but these tend to also be matched pairs with a term on the front and a definition on the back (Lin et al, 2018). When students are asked how they generate flashcards, they report creating cards for the words printed in bold typeface in their textbook-again, matched words and definitions (Senzaki et al, 2017). When there is evidence that flashcard use improves course grade, it occurs in a class that requires matched information on exams, such as listing common symptoms of a disease (Schmidmaier et al, 2011) or identifying definitions of psychology theories (Golding et al, 2012).…”
Section: Ineffective Study Strategiesmentioning
confidence: 99%
“…Together, these results suggest that the WTL assignments enhanced learning relative to studying without explicit instruction to apply this study strategy. This research adds to the body of research focused on helping students develop better study strategies (e.g., Senzaki, Hackathorn, Appleby, & Gurung, 2017).…”
Section: Discussionmentioning
confidence: 99%